2011
DOI: 10.1055/s-0029-1245937
|View full text |Cite
|
Sign up to set email alerts
|

Die Relevanz einer B-Zell-abhängigen Immunpathologie für die Multiple Sklerose

Abstract: In spite of keen clinical and neuroscientific interest, the aetiology and immunopathology of multiple sclerosis (MS) remain to be elucidated. The present work seeks to give insight into the important, but thus far underestimated contribution of B cells to the disease. Emphasis will be placed on the role of B cells as producers of autoantibodies and as antigen presenting cells. In addition, the development of ectopic B cell follicles in the CNS and their potential correlation with the course of the disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We have recently introduced a new model on the C57BL/6 (B6) background, the MBP-PLP fusion protein (MP4)-induced EAE, and we have distinguished several advantages of working with this antigen [ 16 ]. Among these advantages were the chronic disease course and the dependence on B cells and antibodies [ 17 , 18 ]. Our studies have also shown fundamental differences in CNS histopathology when comparing MP4-induced EAE and the traditional MOG peptide 35–55 model with regard to the topography of lesions and the composition of CNS infiltrates [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently introduced a new model on the C57BL/6 (B6) background, the MBP-PLP fusion protein (MP4)-induced EAE, and we have distinguished several advantages of working with this antigen [ 16 ]. Among these advantages were the chronic disease course and the dependence on B cells and antibodies [ 17 , 18 ]. Our studies have also shown fundamental differences in CNS histopathology when comparing MP4-induced EAE and the traditional MOG peptide 35–55 model with regard to the topography of lesions and the composition of CNS infiltrates [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although PrA-based absorbers have been shown to be more effective in pure antibody depletion, the two techniques have not been compared in MS treatment thus far [58]. However, the responsiveness of steroid-refractory MS relapses to apheresis therapy is unlikely to depend on antibody clearance alone, since the clinical course of the disease is not correlated with autoantibody titers, and identification of crucial antibody targets remains elusive [59,60].…”
Section: Resultsmentioning
confidence: 99%